Survei Minat Siswa Mengikuti Pembelajaran Penjas Pada SMA Negeri 1 Tumbang Samba - Akhmad Syarif; Yossita Wisman (FKIP Universitas Palangka Raya, 2023)
This research is motivated by the not maximal learning of physical education. This study aims to determine students' interest in participating in physical education lessons at Tumbang Samba 1 Public High School for the 2020/2021 academic year in Central Katingan District, Katingan Regency. This research is quantitative descriptive. The method used is survey method. The subjects of this research were 44 students of class XI at SMA Negeri 1 Tumbang Samba. The instrument used is a questionnaire. The analysis technique used is pouring the frequency into the form of a percentage. The results of this study indicate that students' interest in participating in physical education learning at SMA Negeri 1 Tumbang Samba is in the moderate category with the highest frequency being in the medium category with 16 students or 36.36%. Students' interest in participating in physical education learning at SMA Negeri 1 Tumbang Samba was in the very high category 3 people or 6.82%, in the high category 9 people or 20.45%, in the medium category 16 people or 36.36%, in the low category 14 people or 31 .82%, and in the very low category 2 people or 4.55%.